Impact of Dysfunctional Leadership on Organizational Performance (Global Journal of Management and Business Research, 2019)
Academic and business literature mostly focuses on the positive traits of the leadership. Even though, there is a surge in the number of research papers published on negative leadership behaviors, there is a gap in literature providing a review of the impact of dysfunctional (or toxic) leadership practices on organizational culture and performance. In this paper, we are defining the key behavioral traits of dysfunctional leaders, categorise them into authoritarian, narcissist, abusive, unpredictable, Machiavellian leadership styles, and provide an overview of the potential impacts that can be observed in organizational behavior and results.